Growth of the Marine Fish-Killing Phytoflagellate, Heterosigma Akashiwo Under Emerging Coastal Regimes: Temperature, Eutrophication and Ocean Acidification - Bronicheski, Cayla M (Scholarship@Western, 2014)
Coastal oceans are fundamental to human economies, nutrition and recreation. Anthropogenic stressors have led to the acceleration of the nitrogen cycle, the accumulation of inorganic carbon in the earth’s atmosphere, the loss of UV-scavenging upper atmospheric ozone and the overall accumulation of deep elements from the earth’s crust to surface exposure. These changes have caused ocean acidification and eutrophication events in coastal waters and the impacts of these events on primary production and ocean biodiversity are not yet fully understood. This study examined the effects of predicted future ocean conditions (salinity, temperature, reduced seawater pH and modified nitrogen supplies), on the growth, photosynthesis and fatty acid composition of a key harmful algal bloom producing phytoflagellate predicted to dominate in the future ocean, Heterosigma akashiwo. Results from H. akashiwo NWFSC were compared to the marine diatom Thalassiosira weissflogii and the marine cyanobacterium, Synechococcus sp. Experimental pH levels represented ambient seawater (pH 8.1 or pH 8.2), and ecologically relevant pH levels predicted for the years 2050 and 2100 (pH 7.4 and pH 7.8, respectively). Findings showed that H. akashiwo experienced maximal growth rates at 20 practical salinity units, which increased with increasing temperatures predicted in a global climate change scenario (from 14.7 °C-24.4 °C). Altering pH environments did not demonstrate any notable change in growth rates of H. akashiwo compared to the other phytoplankton species. Rather, altering the nutrient environment (which occurs in coastal upwelling regimes) was the main driving force to change H. akashiwo productivity and intracellular fatty acid composition. Results from this research can provide a foundation for predicting future ocean acidification impacts on marine ecosystems, economies and fisheries productivity.